Blockchain Technology and its Disruptive Potential in the Digital Economy - Bakri, Asri Ady; Sudarmanto, Eko; Fitriansyah, Novela Deva Puasa Sucifa; Rukmana, Arief Yanto; Utami , Eva Yuniarti (West Science Journal Economic and Entrepreneurship, 2023)
Blockchain technology's disruptive potential in the digital economy has spurred a surge in scholarly interest, leading to a complex landscape of research endeavors. This study employs a comprehensive bibliometric analysis to illuminate the multifaceted dimensions of blockchain's impact. Through analysis techniques and visualization tools, including VOSviewer, we uncover publication trends, influential authors, research themes, collaboration networks, and the interdisciplinary nature of blockchain research. The results reveal a steady increase in publications over the past decade, indicating growing recognition of blockchain's significance. Influential authors emerge as key contributors, shaping the research discourse and driving innovation. Diverse research themes, ranging from fintech and digital transformation to cryptocurrencies and smart contracts, underscore blockchain's applications across various sectors. Collaborative networks highlight the emergence of focused communities, fostering interdisciplinary insights. The integration of VOSviewer facilitates an exploration of these insights, offering a nuanced perspective on blockchain's disruptive potential. Our analysis contributes to a deeper understanding of the evolving landscape, informing researchers, practitioners, policymakers, and stakeholders navigating the complexities of blockchain technology in the digital economy.